A terpyridine based hydrogel system for reversible transmissive-to-dark electrochromism and bright-to-quenched electrofluorochromism. Issue 60 (6th July 2022) - Halder, Sayan; Roy, Susmita; Dixit, Mudit; Chakraborty, Chanchal
Abstract : A terpyridine-based hyrdogelator (TPPCA) with reducible pyridine ring is used as all-in-one hydrogel electrochrome for electrochromic displays (ECDs) for reversible transparent-to-dark electrochromism and bright-to-quenched electrofluorochromism. Abstract : A carboxylic acid-containing terpyridine-based hydrogelator (TPPCA) is synthesized to afford a self-assembly induced TPPCA hydrogel, which was used as an all-in-one electrochrome in electrochromic devices (ECDs) to demonstrate reversible transparent-to-black electrochromism with fast darkening and bleaching time of 8.3 s and 9.5 s, respectively, high photopic coloration efficiency of 65.8 cm 2 C −1 and high optical memory. The ECD also revealed bluish-white to quenched emission simultaneously under the −3.5 V to 0 V voltage range.